Deixis Found in Joe Biden’s Inauguration Speech - Ni Made Ayu Widiastuti; Ni Luh Ketut Mas Indrawati; Kadek Nita Mahasuari (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This research is entitled Deixis found in Joe Biden’s inauguration speech. The aims are to identify deixis types and their functions. The data were collected through the observation method that was done by the note-taking technique. The concept of deixis proposed by Levinson was used to support the data analysis, as well as the qualitative method was used to analyse the selected data into their types of deixis and continued by identifying its functions in the grammatical constituent and the relational information in social deixis. Then, the data analysis was presented using the informal method. The result of the analysis shows that there are five categories of deixis found in Joe Biden's inaugural speech, involving person deixis, place deixis, time deixis, discourse deixis, and social deixis. The functions of each deixis type can be seen in the person deixis which has the function in the form of a personal pronoun. Place deixis has the function of a locative adverb and the adverbial of time is used to express temporal deixis in the speech. Discourse deixis takes the shape of the object of demonstrative pronoun, while social deixis takes the form of relational information to identify a person's authority.